Rumah Singgah Kemah Berkah Sebagai Wadah Penginjilan Dan Penerapan Diakonia Transformatif GKII Di Wilayah Batulicin - Fajar Gumelar; Hengki Wijaya; Ezra Tari (IAKN TORAJA, 2020)
Abstract: The study of this paper originated from the author's anxiety about the appropriate method of training church members. The author tries to provide a new perspective in the formation of new members of the congregation in the form of transformative deacons. The author offers another way of evangelizing and developing a deacon, namely, a shelter for camps. The author uses a descriptive approach to narrating the facts in the field. Data is collected, reduced and then analyzed so that conclusions are drawn from the facts found. The result was that the halfway house had become a place to preach the gospel in the interior of Mount Meratus. This tent house is a learning space for children to know Christ. A halfway house is a place for children to be guided with skills and independence in various daily activities to become human beings with integrity. The facts found in the field show that there are still many children who come from Christian families who do not understand life as a good Christian. The halfway house, the blessed tent, is present not only as a place for learning for children but for parents as well—a halfway house to help children attend. Children are invited to help others in need. Keywords: Halfway House, Evangelism, Transformative Diaconia Abstrak: Kajian tulisan ini berawal dari kegelisahan penulis mengenai metode yang tepat dalam pembinaan warga jemaat. Penulis berusaha memberi perspektif baru dalam pembinaan warga jemaat yang baru dalam bentuk diakonia transformatif. Penulis menawarkan cara lain dalam penginjilan dan pengembangan diakonia yakni rumah singgah kemah. Penulis menggunakan pendekatan dekrriptif untuk menarasikan fakta yang ada di lapangan. Data dikumpulkan, direduksi kemudian dianalisis sehingga ditarik kesimpulan dari fakta yang ditemukan. Hasil yang ditemukan adalah rumah singgah telah menjadi tempat mewartakan injil di pedalaman gunung Meratus. Rumah kemah ini menjadi ruang belajar anak-anak untuk mengenal Kristus. Rumah singgah adalah tempat anak-anak dibimbing keterampilan, kemandirian dalam berbagai kegiatan sehari-hari dengan tujuan supaya menjadi manusia yang berintegritas. Kenyataan ditemukan di lapangan memperlihatkan bahwa masih bayak anak yang berasal dari keluarga Kristen belum memahami hidup sebagai orang Kristen yang baik. Rumah singgah kemah berkah hadir tidak hanya sebagai wadah belajar anak-anak tetapi orang tua juga. Rumah singgah membantu anak dapat madiri. Anak-anak diajak untuk membantu orang lain dalam kekurangan. Kata Kunci: Rumah Singgah, Penginjilan, Diakonia Transformatif